ChemInform Abstract: Regioselective Iodoamination of Terminal Ynamides for the Synthesis of α‐Amino‐β, β‐diiodo‐enamides. Issue 29 (29th June 2016) - Huang, Hai; Tang, Luning; Han, Xiaobo; He, Guangke; Xi, Yang; Zhu, Hongjun
Abstract: Intermolecular iodoamination of alkynes to diiodoenamines is achieved for the first time.